PENGARUH IMPLEMENTASI APLIKASI SISTEM KEUANGAN DESA (SISKEUDES) TERHADAP KUALITAS LAPORAN KEUANGAN DESA DI KECAMATAN MAIWA - Maryam Maryam; Kamaruddin Sellang; Erfina Erfina (JIA: Jurnal Ilmiah Administrasi, 2021)
Every village financial report presented must be of high quality and accountable to the public because the report can later be used by policy makers to make decisions in the administration of government. One of the things that affect the quality of financial reports is the Village Financial System (Siskeudes) used. The purpose of this study was to determine the effect of the implementation of the Siskeudes application on the quality of village financial reports in Maiwa District, Enrekang Regency. The method used in this research is descriptive with quantitative analysis using George C Edward III's policy implementation model. The population in this study is the village secretary and village finance officer in Maiwa District, Enrekang Regency. Samples were taken from 42 respondents using saturated sampling. Data were analyzed by Likert scale. Based on the research results, it can be seen that from the results of the Siskeudes application implementation test, the percentage is 76.325% in the "good" category and the quality of financial reports is 86.08% in the very good category. The implementation of the Siskeudes Application has a significant effect on the Quality of Village Financial Reports in Maiwa District, Enrekang Regency. Based on the value of tcount ttable or 7.850 2.021 so that H0 is rejected and Ha is accepted. Implementation of the Siskeudes Application (X) has an effect of 60.6% on the quality of financial reports (Y). Every 1% increase in the implementation variable of the Siskeudes application will improve the quality of financial reports. The coefficient is positive, meaning that there is a positive relationship between the implementation of the Siskeudes application and the quality of financial reports, the higher the implementation of the Siskeudes application, the higher the quality of financial reports.